2013
DOI: 10.1158/0008-5472.can-13-0982
|View full text |Cite
|
Sign up to set email alerts
|

SHON Is a Novel Estrogen-Regulated Oncogene in Mammary Carcinoma That Predicts Patient Response to Endocrine Therapy

Abstract: Endocrine therapies are the primary systemic intervention for patients with estrogen receptor-positive (ER þ ) breast cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 46 publications
(38 reference statements)
2
23
0
Order By: Relevance
“…We previously showed that SHON was able to oncogenically transform the immortalized normal human mammary epithelial cell line MCF10A . To determine whether SHON is involved in EMT, we first stably overexpressed SHON in MCF10A cell line, and the expression was confirmed by immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that SHON was able to oncogenically transform the immortalized normal human mammary epithelial cell line MCF10A . To determine whether SHON is involved in EMT, we first stably overexpressed SHON in MCF10A cell line, and the expression was confirmed by immunoblotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the SHON ‐expressing plasmid pIRESneo3‐SHON and the pIRESneo3 empty vector, the SHON ‐specific siRNA‐expressing plasmid pSilencer 2.1‐U6‐shSHON (shSHON) and the negative siRNA control pSilencer 2.1‐U6 (shCtrl) were previously described . The constructions of the SHON‐flag fusion expression plasmid and the stable cell lines are detailed in Supporting Information for Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations